Interpersonal synchrony: Interaction variables and gender differences in preschoolers with ASD - Paolizzi, Eleonora; Bertamini, Giulio; Bentenuto, Arianna; Venuti, Paola (Frontiers in Psychiatry, 2022)
Background: Females with ASD tend to be under-recognized as they might present a different symptom manifestation, better social abilities, and masking behaviors. Since the main limitation of current literature on gender differences is represented by focusing on broad constructs, research needs to prioritize narrower constructs related to the subdomains of social abilities. Hence, the aim of this work was to explore gender differences in Interpersonal Synchrony of children with ASD. Method: N=51 psychologist-child dyads, 25 females and 26 males participated in the study. An Observational Coding Scheme to study interaction features was applied to video-recorded sessions of the ADOS-2 administration. Results: Females presented more synchronous behaviors with shorter latencies. Their interplays were longer, more complex, more engaging and most frequently adequately concluded with respect to males. The complexity of interchanges, their total duration and the proportion of exchanges adequately terminated correlated with the Social Affect score, Personal-Social, and Language Quotients in females, but not in males. The success rate of psychologist proposals correlated with Language Quotient in both males and females. The number of exchanges positively correlated with the Performance Quotient in males. Despite females being significantly older than males, age-related differences did not emerge. Conclusions: Our findings suggest the importance of studying gender differences with respect to interaction variables. Females may present better IS abilities which, in turn, may promote social and language development. Further, our results suggested that successful interactions seem to rely more on social abilities in females, while males appeared to rely more on performance skills.